Virtual Learning Objects As Support Tool To The Ie “José Maria Berástegui’s” Secondary Teachers - Pérez González, Luis G.; Cogollo López, Meriele (Ingeniería Solidaria, 2010)
This article presents the research project “Design of Virtual Learning Objects” proposed as tool to support secondary teachers from the IE “José Maria Berástegui”, located at the Berástegui village, Municipality of Ciénaga de Oro - Córdoba. It explains the creation of the Virtual Learning Objects (VLO) in order to support the teaching work in the pointed institution; it describes the combination of the pedagogic aspects used for the design of these objects with the technological hardware to create the virtual ambience.